BUILD BACK BETTER STRATEGY AND MODERNIZATION OF KUA SERVICES POST-HYDROMETEOROLOGICAL DISASTER IN LANGSA CITY - Rafika Rahman (STAI Nusantara Kota Banda Aceh, 2026)
The extreme hydrometeorological disasters that struck the coastal area of Langsa City in late 2025 have explicitly exposed systemic vulnerabilities in public service infrastructure, particularly within the Religious Affairs Office (KUA). The destruction of electronic work devices and the severe threat of decay to the community's sacred civil documents due to floodwaters demand a substantially more resilient recovery strategy, rather than mere architectural restoration. This policy paper critically examines the disparity in the 2026 recovery budget allocation, where a massive fund of Rp 505,320,000 is exclusively focused on rebuilding physical structures, while crucial investments in digital archive mitigation are entirely neglected. Employing a qualitative approach through a case study design, this research gathered primary data from 30 KUA apparatus respondents and reviewed national strategic documents. Diagnosis using the SWOT quadrant matrix places the institution in a Turn-Around position, urging immediate internal reform. Furthermore, testing policy alternatives using William Dunn's evaluative parameters proves that a purely physical repair strategy is a glaring inefficiency for the state. As a concrete solution, this study recommends a physical-digital integration strategy within the Build Back Better framework through the revision of the Operational Activity Guidelines (POK). This tactical step synergizes rehabilitation funds with the procurement of high-speed scanners and cloud repository systems, ensuring that the civil identity rights of the community remain eternally alive and protected, transcending any future climate crises. Keywords: Hydrometeorological Disaster, Build Back Better, Religious Affairs Office (KUA), Digital Archives, Public Policy.